2022
DOI: 10.3389/fpubh.2022.857873
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Clinical Characteristics of Nosocomial Infection in Adult Patients Undergoing Extracorporeal Membrane Oxygenation: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThis study conducts a meta-analysis of clinical outcomes of nosocomial infection in adult patients receiving extracorporeal membrane oxygenation (ECMO) and systematically evaluates clinical epidemiological characteristics.MethodsDocument retrieval strategies were determined, and all adult patients treated by ECMO were included. The prevalence, incidence, mortality, ECMO use time, intensive care unit (ICU) stay time, hospital stay time, and risk factors of nosocomial infection were systematically evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…A recent study showed that relapses and superinfections occurred in 79% of COVID-19 patients assisted with ECMO [ 15 ]. The challenge of a VAP diagnosis in this population may have induced misdiagnoses and delayed appropriate therapy [ 5 , 35 ]. Thus, it may have increased the burden of VAP, while favoring the risk for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that relapses and superinfections occurred in 79% of COVID-19 patients assisted with ECMO [ 15 ]. The challenge of a VAP diagnosis in this population may have induced misdiagnoses and delayed appropriate therapy [ 5 , 35 ]. Thus, it may have increased the burden of VAP, while favoring the risk for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that patients receiving ECMO treatment may require more analgosedation, a more intense anticoagulation, and may be sicker overall. For instance, studies reported higher infection rates among patients who were ECMO-treated compared to patients who were non-ECMO-treated [ 32 , 33 , 34 ]. Moreover, we observed a longer treatment duration in the ECMO subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that MDR infections were related to poor prognosis of ECMO patients as aspect excepting mortality. A meta-analysis suggested that the infections in ECMO patients increased mortality by 32percentt [3]. But compared with Group N, Group R of patients did not exhibit higher mortality, which may be explained by the range of patient selection [8].…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving ECMO treatments are high risk for MDR infections due to the immunode ciency caused by severe illness and the applications of invasive life support measures [5]. It is con rmed that MDR infections in ECMO patients and delayed treatment associated with increased mortality [2,3]. Timely and targeted empiric antibiotic therapies against MDR pathogens are associated with reduced mortality [2].…”
Section: Introductionmentioning
confidence: 99%